Crystallization and preliminary X-ray analysis of the mRNA-binding domain of elongation factor SelB from Escherichia coli in complex with RNA - Soler, Nicolas (International Union of Crystallography, 2007)
In bacteria, selenocysteine (the 21st amino acid) is incorporated into proteins via machinery that includes SelB, a specific translational elongation factor. SelB binds to an mRNA hairpin called the selenocysteine-insertion sequence (SECIS) and delivers selenocysteyl-tRNA(Sec) to the ribosomal A site. The minimum C-terminal fragment (residues 478–614) of Escherichia coli SelB (SelB-WH3/4) required for SECIS binding has been overexpressed and purified. This protein was crystallized in complex with 23 nucleotides of the SECIS hairpin at 294 K using the hanging-drop vapour-diffusion method. A data set was collected to 2.3 Å resolution from a single crystal at 100 K using ESRF beamline BM-30. The crystal belongs to space group C2, with unit-cell parameters a = 103.50, b = 56.51, c = 48.41 Å. The asymmetric unit contains one WH3/4-domain–RNA complex. The Matthews coefficient was calculated to be 3.37 Å(3) Da(−1) and the solvent content was estimated to be 67.4%.